Molecular characterization, tissue distribution and functional analysis of galectin 1-like 2 in grass carp (Ctenopharyngodon idella). Issue 94 (November 2019) - Zhu, Denghui; Fu, Peipei; Huang, Rong; Xiong, Lv; Wang, Yumeng; He, Libo; Liao, Lanjie; Li, Yongming; Zhu, Zuoyan; Wang, Yaping
Abstract: Galectins, as an evolutionary conserved group of lectin superfamily, has the functions of pathogen recognition, anti-bacteria and anti-virus. In this study, a 405 bp cDNA sequence of galectin 1-like 2 ( CiGal1-L2 ) was obtained from grass carp ( Ctenopharyngodon idella ), which encoded 134 amino acids with a predicted molecular mass of 15.143 kDa and an isoelectric point of 5.33. The sugar binding motifs (H–N-R, V–N and W–E-R) were detected in carbohydrate-binding domain (CRD). The amino acid sequence similarity showed that CiGal1-L2 was 40.30–42.54% and 66.42–81.20% similarity to mammalian and fish counterparts, respectively. The phylogenetic tree showed that CiGal1-L2 was clustered with fish galectin-1s and closely related to Cyprinus carpio . Real-time quantitative PCR (RT-qPCR) analysis revealed that CiGal1-L2 was widely expressed in all tested tissues. In addition, the expression of CiGal1-L2 was differentially up-regulated challenged with grass carp reovirus (GCRV), lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (poly I:C). The fluorescence of CiGal1-L2-GFP was distributed in the cytoplasm and nucleus of HEK 293T cells and showed a trend of nuclear translocation after LPS and poly I:C treatment. Finally, the recombinant CiGal1-L2 (rCiGal1-L2) protein showed strong binding ability to LPS. In conclusion, the results provided further insight into the immune roles of galectin-1 in teleost. Highlights: CiGal1-L2 was widely expressed in all tested tissues. CiGal1-L2 transcripts were induced by various stimulations. The fluorescence of CiGal1-L2-GFP showed a trend of nuclear translocation after LPS and poly I:C treatment. The recombinant CiGal1-L2 protein showed strong binding ability to LPS.